Optimization of Software Testing Processes Through a Quality Management System - Maya E.I Munaiseche; Radea Aditya Putra Mohamad; Immanuel Naharia; Stive Immanuel Ante; Dave Immanuel Lilonsili (Cerdika: Jurnal Ilmiah Indonesia, 2026)
Background: The development of technology, both hardware and software, is rapidly advancing due to the growth of Artificial Intelligence (AI), which simplifies many human activities, including the software testing process. This research journal discusses how software testing is conducted through a Quality Management System (QMS). Objective: The journal examines whether software testing processes are related to QMS, how significantly QMS supports software testing, and the differences between testing with QMS and without QMS. Methods: This study outlines the stages of software testing through QMS, such as Software Quality Assurance (SQA), Quality Control (QC), Test Maturity Model Integration (TMMI), and performance indicators. According to the American Society for Quality (ASQ), QMS is a formal and documented system consisting of policies, processes, and procedures designed to achieve an organization's quality policies and objectives. Results: Several experts also define QMS as a system that focuses on improving customer satisfaction, process consistency, efficiency, and the overall quality of products or services. Software, according to Roger S. Pressman, is a set of instructions (programs), data structures that allow information manipulation, and related documentation describing operations and functions. Conclusion: Overall, QMS not only improves software product quality but also strengthens the testing process, making it more optimal, efficient, and aligned with organizational goals. The integration of QMS frameworks such as ISO 9001:2015, CMMI, and TMMI provides organizations with a competitive advantage by ensuring consistent delivery of high-quality software products that meet or exceed customer expectations.